Soarer's choice - Modesitt, L. E., Jr., 1943- (Modesitt, L. E., Jr., 1943- Corean chronicles, 2006)
Millennia ago, a magical disaster caused the fall of a great worldwide civilization, the end of a golden age. New civilizations have fought their way up from the ancient destruction and chaos, knowing little of the lost world that preceded them or the details of its fall. Corus today is a world of contending countries, of humans, but also of strange animals and supernatural creatures. It is a place of magical powers, and of a few people who are talented enough to use them. The time is at hand for the great move, for Corus to be abandoned by the civilizing forces of the government of Alectors. Dainyl and Mykel are trying to hold everything together as all the systems on Corus are failing. But the mysterious Ancients, the Soarers, may hold a powerful and destructive trump card.